Pengaruh Pengawasan dan Kondisi Kerja terhadap Keterlibatan Kerja Karyawan Rumah Sakit Mata Undaan Surabaya - Fitri Widyacahya (Universitas Airlangga, 2018)
Preliminary survey result showed the employee job involvement rate of Rumah Sakit Mata Undaan Surabaya reached 65,26%. It means that the employee's job involvement rate was low (standard 80%). Job involvement consists of three factors; support from co-workers, employee's participation in decision making, and the dependence of the tasks. The aim of this study was to analyze the influence of supervision and working condition of employee job involvement. The observational analysis was used in this research with the cross-sectional design. The data were obtained through questionnaires with simple random sampling as many as 62 employees as the sample. The obtained data were analyzed with logistic regression test univariate (α=0,05) to examine the influence of supervision and working condition of the employee's job involvement. The test result indicated that supervision significantly influenced employee's job involvement at significance value was0,000201. Better supervision made better employee's job involvement. On the other hand, working condition did not influence the employee's job involvement (significance value was 0,097), but cross-tabulation result indicated that better working condition made better employee's job involvement. It can be concluded that supervision affects job involvement while working condition does not affect the job involvement.   Keywords: job involvement, supervision, working condition